[Eastern Telecom case ; Sexual abuse at home ; Singing telegrams [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
A report on charges of crony capitalism and unfair treatment of shareholders in Eastern Telecoms. Looks at the children who are sexually abused at home. A piece of birthday greetings brought to your home via singing telegram.
Eastern Telecom case (17 min.) -- Sexual abuse at home (15 min.) -- Singing telegrams (12 min.)
VHS.
Keywords: Eastern Telecommunications, Inc; Philippine Telephone and Telegraph Company; Child sexual abuse; Sexually abused children; Telegraph -- Employees. -- Philippines